Hydrophobization method and "Ramksis-2" material for the flow rate in crease in the watered oil wells - Babaev, V. N.; Kaptsov , I. I.; Nalyvaiko , O. I. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
In the article there is made an attempt to investigate the most effective methods of petrofeedback increasing and wells productivity in the conditions of Ukrainian oil and gas fields. Traditional methods petrofeedback increasing and new approaches of solving this problem, such as hydrophobization layer zones or the use of water-swellable polymers are also considered. Particular attention is given to the processing of studies of cores of flooded wells to determine the coefficient of permeability recovery after injection of hydrophobic suspension "Ramsinks-2". The material significantly increases the injectivity of the well, reduces the injection pressure by improving permeability of the formation. It is shown that the use of hydrophobic materials "Ramsinks-2" and "Silpan-SV" in wells allows almost completely restore the filtration characteristics of the producing formation by increasing the oil component in the oil-water mixture.